Film as Medium for Struggling (Social Activism of Indonesian Women Film Producers in Post-Reformation Era) - Daris Dzulfikar; Galuh Gita Indrajayani (Journal of Feminism and Gender Studies, 2026)
This study analyzes the role of women film producers in Indonesia post-reformation in utilizing film as a medium for social activism, both directly and indirectly. This study examines how Indonesian women film producers create social impact by producing films that address social, educational, and human rights issues, using the impact dimension theory popularized by Diana Barrett and Sheila Leddy. Through a qualitative approach with literature review methods, this research identifies narrative strategies, themes from the films they explore, and the potential impact of their works on driving social change. This research provides a new perspective on the role of women producers in constructing narratives and influencing the impact of their films. The results reveal that films play several important roles: through compelling stories, films can touch emotions; awareness to raise information and stimulate discussion; dimensions engagement to create real interaction from the audience; then the stronger movement which inspires new institutional practices; and ultimately occurs social change, to encouraging tangible action. This is all due to the role of women producers, who are not only have function in technical and financial, but also artistic and social activists who bring new perspectives, promote inclusivity, and empower communities.